Recollection of ICU admission - Turner_JS (Department of Medicine, 2023)
This study prospectively evaluates the recall of one hundred patients following admission to an Intensive Care Unit (ICU) at Groote Schuur Hospital. It was prompted by criticism (by members of staff and visitors to the ICU) of our practice of wardrounds, arterial blood gas sampling, and light sedation of patients. In addition, staff preconceptions about patients' reactions to the ICU needed evaluation. The patients analyzed included a wide spectrum of race, religion, occupation, and educational levels. The more common diagnoses included asthma (22%), pneumonia (14%), trauma (13%), and Adult Respiratory Distress Syndrome (ARDS) (13%). The average APACHE II score (a scoring system widely used to evaluate severity of illness) was 12.27 and 68% of the patients were mechanically ventilated. Objective data collected while the patients were in the ICU included demographic information, diagnosis, APACHE II score, sedation, level of consciousness, and procedures. Within 48 hours of discharge from the ICU, patients were interviewed and asked to quantify their recall of procedures and events which had occurred while they were in the ICU. Data was entered into a microcomputer database for analysis and, where appropriate, statistical tests were performed. Seventy-one patients recalled being admitted to hospital but only 50 remembered being admitted to ICU. Eighty-four patients described the ICU atmosphere as friendly or relaxed. Seventy-three patients felt that they had sufficient sleep while in the ICU. The most frequently reported unpleasant experiences were arterial blood gas sampling (48 patients), tracheal suctioning (30 of 68 ventilated patients), pain (22 patients), and noise (20 patients). Only 6 patients disliked wardrounds and discussion around the bedside. Conclusions include the suggestions that arterial catheters or pulse oximetry should be used when frequent arterial blood gas analyses are needed, and that tracheal suctioning should be performed with more care.